Analisis Penerapan Etika Bisnis Islam di Pasar Inpres Palu - Nurfitriani, Nurfitriani (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
The sale and purchase transaction also took place in the city of Palu at one of the traditional markets, namely the Palu Inpres Market. In this market, there are various kinds of staple goods traders ranging from vegetables, side dishes, spices, fruit, clothes and other basic necessities. This research aims at realizing Islamic business ethics in the market in Palu. This type of research is field research and a qualitative approach. Information in this research is sellers and buyers who carry out transactions in the presidential market in Palu. The results showed that some of the sellers had implemented Islamic business ethics while some had not applied Islamic business ethics with the reason of obtaining greater profits.